Sairaanhoitajia Filippiineiltä näkökulmia kestävään kansainväliseen rekrytointiin - Pitkänen, Pirkko (Tampere University Press, 2018)
Nurses have been recruited to Finland from the Philippines since 2008. Although the numbers are relatively low, the phenomenon is new and has thus given rise to a manifold societal debate. It has been questioned, whether the international recruitment of nurses is an ethically and economically sustainable solution to the shortage of nursing staff in Finland. This publication serves as a forum where various agents in the international recruitment processes can get their voice to be heard. A multi-perspective approach is used to enable researchers to provide a fair, equivalent and empirically-validated illustration of the causes and consequences of international recruitment processes.